Leveraging Social Media in The College Classroom - Stephanie West; Katie Archer Olson; Rick Holbeck (Journal of Scholarly Engagement)
This paper explores the integration of social media platforms into higher education to enhance student engagement, foster collaboration, and promote meaningful learning experiences. Drawing upon a comprehensive review of existing literature, empirical evidence, and practical insights, the study investigates the implementation of various social media projects within educational contexts. The research examines the effectiveness of diverse social media initiatives, including infographics, memes, blog posts, TikTok-style public service announcements, and podcast scripts, in facilitating student learning and participation. Moreover, the paper identifies key challenges encountered during the integration process, such as technical hurdles, alignment with course objectives, and ethical considerations, and proposes strategies for addressing theses challenges. Additionally, the study explores promising future directions for refining the use of social media in education, including integrating emerging technologies, evolving pedagogical approaches, and prioritizing ethical considerations. Through a reflective analysis of successes, shortcomings, and lessons learned, this paper provides valuable insights for educators, instructional designers, and educational policymakers seeking to leverage social media effectively in higher education. Ultimately, the research contributes to a deeper understanding of the role of social media in promoting student engagement, facilitating learning, and shaping the future of education in a digital age.